Evidence‐based safety profile of oral ketorolac in adults: Systematic review and meta‐analysis - Vicente Esparza‐Villalpando; Gladys Ortiz‐Barroso; David Masuoka‐Ito (Pharmacology Research & Perspectives)
Abstract The primary objective of the present review was to report the safety profile of oral ketorolac in adults using the systematic review and meta‐analysis methodology based on clinical trials. The present study is a PRISMA‐based systematic review and risk ratio (RR) meta‐analysis of the adverse events reported in clinical trials that used oral ketorolac; the review includes 50 clinical trials. The RR for the comparison of a single intake of oral ketorolac versus placebo, including all types of adverse events, was RR = 2.59, IC95% (1.5102; 4.4360) with p = 0.02, the RR for the comparison of a multiple intakes of oral ketorolac versus placebo for all types of adverse events was RR = 1.39, IC95% (0.95; 2.05) with p = 0.093, the RR for the comparison of a single intake of oral ketorolac versus active drugs for all types of adverse events was RR = 0.61, IC95% (0.49; 0.77) with p < 0.0001, the RR for the comparison of multiple intakes of oral ketorolac versus active drugs for all types of adverse events was RR = 0.78, IC95%(0.65; 0.93) with p = 0.006. Multiple intakes of 5, 10, or 20 mg of oral ketorolac, in treatment over 1–10 days, do not increase the risk of adverse events compared to placebo and show a tendency to reduce the risk of adverse events compared to active drugs. When a single intake of ketorolac (5, 10, 20, or 30 mg) is compared to a placebo, the risk increases only for trivial and mild adverse events.